Genomic Identification of RNA Editing Through Integrating Omics Datasets and the Clinical Relevance in Hepatocellular Carcinoma - Chen, Juan; Wang, Lu; Wang, Fangbin; Liu, Jian; Bai, Zhenyu (Frontiers in Oncology, 2020)
RNA editing is a widespread post-transcriptional mechanism to introduce single nucleotide changes to RNA in human cancers. Here, we characterized the global RNA editing profiles of 373 hepatocellular carcinoma (HCC) and 50 adjacent normal liver samples from The Cancer Genome Atlas (TCGA) and revealed that most editing events tend to occur in minor percentage of samples, with moderate editing degree (20-30%). Moreover, these RNA editing prefer to be A-to-I RNA editing in protein coding genes, especially in 3'UTR regions. Considering the association between DNA mutation and RNA editing, our analysis found that RNA editing maybe a complementary event for DNA mutation of HCC risk genes in HCC patients. We next identified 454 HCC related editing sites, and many locate on the same genes with same editing patterns. The functional consequences of editing revealed 2086 functional editing sites and demonstrated that most editing in coding regions are non-synonymous variation. Furthermore, our results showed that editing in 3'UTR regions tend to influence miRNA-target binding, and the editing degree seems to be negatively correlated with gene expression. Finally, we found 46 HCC related editing sites with consequence are able to distinguish the prognosis differences of HCC patients, suggesting their clinical relevance. Together, our These results highlight RNA editing as a valuable molecular resource for investigating HCC mechanisms and clinical treatments.